Dual effect of dietary seaweed of extract nanoparticles (GNS) with bionanocomposite cellulose acetate membranes (CA/bio-AgNps) on growth performance and health status of the Nile tilapia (Oreochromis niloticus): Specification on feed utilization, immune system, and antiparasitic action - Radwan, Mahmoud; El-Sharkawy, Mahmoud A.; Negm, Mohammed A.; Mohammadein, Amaal; Malki, Jamila S. Al; Al-Thomali, Asma W.; Mohamed, Ahmed M.; Yassir, Shahd; Bashar, Mansour A.E. (Frontiers in Marine Science, 2022)
Seaweed draws a lot of attention for its vital role in aquaculture as it contains beneficial biological compounds, which undoubtedly might help in the development of this field. The current study sheds the light on potential efficiency of dietary supplements of Grateloupia acuminata and G. doryphore (Halymeniaceae) nanoparticles (GNS) at different levels with bio-nanocomposite cellulose acetate membranes (CA/bio-Ag Nps) on improved growth performance, digestive enzyme activity, immunity, antioxidative, resistance against infectious pathogens and characterization of water quality treated with (CA/bio-Ag Nps) that is used in rearing Nile tilapia (Oreochromis niloticus). Four concentrations (0.1, 0.25, 0.5 and 1.0 ml/L) of GNS extract were tested as potential anti-bacterial and for the efficacy of being parasitic. Fish with average weight (24.46 ± 0. 50 g) was apportioned as six experimental groups (T0, T1, T2, T3, T4, and T5) represented as (0.0 GNS, 0.0, 0.1, 0.25, 0.5, and 1.0 % GNS in diets with CA/bio-Ag Nps, respectively. Injected fish with Aeromonas hydrophila were performed at the end of trial. Chemical and bacteriological water indices significantly showed improvement after being treated with (CA/bio-Ag Nps) than control group. Growth, carcass composition, digestive enzyme, hematological and biochemical indices were significantly noticed positive (p < 0.05), especially T4 and T5, than control group. In parallel, a significant improvement was noticed in serum lysozyme, total immunoglobulin, complement C3, antioxidative enzyme and the relative expression of hepatic and inflammatory genes with an increased level of GNS (P < 0.05) are upregulated than control group. Remarkably, GNS supplemented diets and extracted provided positive efficacy against A. hydrophila with decreased percentage of fish mortality besides efficacy on anti-bacterial strains and Cichlidogyrus Tilapiae respectively. To sum up, the seaweed extract with (CA/bio-Ag Nps) resulted in better growth performance of fish, anti-pathogenic effect, and health status. Furthermore, (CA/bio-Ag Nps) was vital in improving water characters; it should be studied and applied more in future.